PPARs and the Development of Type 1 Diabetes. (9th January 2020) - Holm, Laurits J.; Mønsted, Mia Øgaard; Haupt-Jorgensen, Martin; Buschard, Karsten
Abstract : Peroxisome proliferator-activated receptors (PPARs) are a family of transcription factors with a key role in glucose and lipid metabolism. PPARs are expressed in many cell types including pancreatic beta cells and immune cells, where they regulate insulin secretion and T cell differentiation, respectively. Moreover, various PPAR agonists prevent diabetes in the non-obese diabetic (NOD) mouse model of type 1 diabetes. PPARs are thus of interest in type 1 diabetes (T1D) as they represent a novel approach targeting both the pancreas and the immune system. In this review, we examine the role of PPARs in immune responses and beta cell biology and their potential as targets for treatment of T1D.